Prospects for the introduction of training to improve knowledge, skills and practical skills in the specialty «Dentistry» for family doctors at the Department of Orthopedic Dentistry of the National University of Health of Ukraine named after P. L. Shupyk - Bida Віталій Іванович; Doroshenko Олена Миколаївна; Volosovets Тетяна Миколаївна; Leonenko Павло Вікторович; Omelianenko Ольга Анатоліївна; Doroshenko Максим Віталійович; Andrusenko Алла Сергіївна (Actual Dentistry, 2023)
Relevance. Dental diseases, including dentoalveolar anomalies, have a significant prevalence and occupy a leading place in the structure of the general morbidity of the population of Ukraine. In the context of a pandemic and a state of war, the effectiveness of preventive measures has fallen sharply, which negatively affects the dental health of the population. An important role in solving this problem should be taken by family doctors, who are representatives of the primary level of health care. A family doctor should take a leading place in the prevention and detection of diseases, including dental diseases, pay special attention to hygiene education and education of the population, health education. Therefore, much attention has recently been paid to an interdisciplinary approach in dentistry, which will significantly improve the effectiveness of patient treatment. Purpose – scientific and methodological substantiation of the need for continuous professional development of general practitioners in dental care for the population at the dental departments of the National University of Health of Ukraine named after P.L. Shupyk. Results. Priority areas for training general practitioners in the preservation of dental health have been identified. Conclusions. Awareness of the family doctor with preventive dental measures will make it possible to bring primary medical care closer to the population, ensure its quality and accessibility, prevent the development of severe pathology and conduct appropriate comprehensive, including orthopedic treatment.